Neutropenia in adults – significant diagnostic issue - Stefaniuk, Paulina; Szymczyk, Agnieszka; Podhorecka, Monika (Nursing in the 21st Century, 2018)
NEUTROPENIA IN ADULTS – SIGNIFICANT DIAGNOSTIC ISSUE Introduction. Neutropenia, a disorder quite commonly encountered in blood tests, is defined as a decrease in the absolute neutrophil count below 1500/μl. Neutropenia may not be clinically significant, whereas it sometimes indicates serious haematological, infectious or rheumatic diseases. The reduction of the number of neutrocytes below 500/μl is referred to as ’agranulocytosis’. Such decrease in neutrophil count impairs host defense and makes the patient more vulnerable to bacterial and fungal infections, which may lead to life-threatening sepsis. Aim. This review presents the causes of congenital and acquired neutropenia, with particular attention to drug-induced neutropenia, which may occur due to the intake of the broad spectrum of drugs, including over-the-counter drugs. The article also attempts to answer the question of how the neutropenia and agranulocytosis should be diagnosed and treated. Methods. The publication is based on the analysis of the literature (PubMed database). Results. It has to be emphasized that a thorough physical examination and appropriate additional tests make it possible to diagnose a disease that causes neutropenia. This allows for the implementation of appropriate therapeutic procedures, and consequently, leads to avoidance of serious infections.